Synergistic biocontrol of Phthorimaea operculella: solvent-dependent interactions between entomopathogenic nematodes and Achillea millefolium extracts - Davoud Mohammadi; Nazila Mahin Allahverdizadeh; Hasan Valizadeh; Naser Eivazian Kary (Biological Control)
The potato tuber moth, Phthorimaea operculella is a highly destructive pest of potato crops, causing significant losses in both field and storage conditions. Due to the environmental and health risks posed by synthetic pesticides, as well as increasing insecticide resistance, sustainable alternatives for integrated pest management (IPM) are urgently needed. This study investigates the synergistic potential of Achillea millefolium (yarrow) extracts and three entomopathogenic nematodes (EPN) species including Steinernema carpocapsae, S. feltiae and Heterorhabditis bacteriophora against P. operculella larvae. Bioassays were conducted on first-instar (3-day-old) larvae reared on potato tubers under controlled conditions. Yarrow aerial parts were extracted via maceration using hexane, ethyl acetate, methanol, and water solvents. The insecticidal effects of individual and combined treatments were assessed, with LC50 values calculated for each. Key findings revealed that the methanol extract exhibited the highest larvicidal activity (LC50 = 9.030 g/L), while the ethyl acetate extract was least effective (LC50 = 24.898 g/L). Among EPNs, S. carpocapsae was the most virulent (LC50 = 34.88 IJ/100 µL), whereas H. bacteriophora showed the lowest efficacy (LC50 = 114.3 IJ/100 µL). Notably, the methanol extract negatively impacted all three EPN species, exhibiting complete antagonism in combined treatments. In contrast, ethyl acetate extract demonstrated the strongest synergistic effect with EPNs. Greenhouse trials, conducted at 10 × LC50 concentrations, confirmed that combined treatments significantly reduced larval mining damage compared to individual applications. These findings highlight the potential of A. millefolium-EPN combinations as a sustainable IPM strategy against P. operculella, with solvent selection critically influencing compatibility.